THE EFFECT OF SERVICE QUALITY AND PRICE PERCEPTION ON CUSTOMER SATISFACTION AT THE ALBASIKO II COOPERATIVE ELECTRONICS UNIT - Mardahleni Mardahleni; Roza Gustika; Wildan Wildan (Journal of Social and Economics Research, 2026)
This study aims to determine the influence of service quality and price perception on customer satisfaction at the Albasiko II Cooperative’s Electronics Unit in West Pasaman Regency. Service quality was measured using indicators such as performance, reliability, aesthetics, service capability and empathy. Price perception indicators included product affordability, price-quality alignment, price-benefit alignment, and price competitiveness. This study employed a quantitative approach using an associative method and purposive sampling, a non-probability sampling technique in which not all members of the population have an equal chance of being selected. The sample comprised 96 respondents, all of whom were customers of Albasiko II Electronics. Data collection was carried out via a questionnaire and analysed using multiple linear regression with SPSS version 26 software. The results indicate that service quality and price perception have a significant and positive influence on customer satisfaction, both individually and simultaneously. These findings highlight that efforts to improve customer satisfaction should focus on providing high-quality service and implementing strategic pricing. It is hoped that this study will provide valuable insights for business practitioners and academics in understanding the dynamics of consumer behaviour and in developing more effective and sustainable marketing strategies.